Breast Milk Bank Laws In The Perspective of The Kaidah Fikih Dar’ Al-Mafᾱsid Muqadam A’Lᾱ Jalb Al-Mashᾱlih - Abd Rouf (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
This research was conducted in order to know breast milk Bank Laws in the perspective of the kaidah fikih dar’ al-mafᾱsid muqadam a’lᾱ jalb al-mashᾱlih, This research is a literature study, the data of which is sourced through journals, books, encyclopedias, magazines, and documents. The approach used is the tarjih approach, which is to collect two contradictory arguments and then look for the point. If no common ground is found, then one of the two arguments is favored. With this method, it is hoped that research on breast milk bank law will produce laws that are more appropriate and relevant in Indonesia. The results of the study show that 1) that the collection of breast milk by the breast milk Bank can cause a mix of lineages between babies who consume breast milk from all women who donate it. So the existence of an breast milk bank is contrary to maqāṣid al-Sharī‘ah which is in the form of maintaining nasab/ḥifẓ al-Nasb. After reviewing the establishment of breast milk banks in Indonesia by looking at the diverse social conditions and the low level of public understanding of the impact of breastfeeding (raḍāʽ), the legality of breastfeeding banks is something that must be prevented, (2) There is a high possibility that marriages are forbidden, as a result of mixing breast milk from the donors, (3) a statement from the team of doctors stating that the need for a breast milk bank is not too urgent. So the law for establishing an breast milk bank in Indonesia is from the perspective of the fiqh rules of dar' al-Mafᾱsid muqaddam alā jalb al-Maṣhāliḥ, so from the above review it can be concluded that it is unlawful to establish an breast milk bank. Considering that the disadvantages of a breast milk bank outweigh the benefits. The argument that breast milk banks are urgent due to many natural disasters, premature babies, and so on can actually be overcome by breastfeeding their children to their nursing mothers.Penelitian ini dilakukan agar dapat diketahui hukum bank ASI perpektif  kaidah fikih dar’ al-mafᾱsid muqadam a’lᾱ jalb al-mashᾱlih, Penelitian ini merupakan studi kepustakaan, yang datanya bersumberkan melalui jurnal, buku, ensikolopedi, majalah, dan dokumen. Pendekatan yang digunakan yakni pendekatan tarjih yaitu mengumpulkan dua argumentasi yang bertentangan kemudian dicari titiknya. Bila tidak ditemukan titik temu, maka diunggulkan salah satu dari kedua argumen tersebut. Metode ini diharapkan penelitian mengenai hukum bank ASI menghasilkan hukum yang lebih sesuai dan relevan di Indonesia. Hasil Penelitian menunjukkan bahwa 1) Bahwa pengumpulan ASI yang dilakukan Bank ASI dapat menyebabkan percampuran nasab antara bayi yang mengkonsumsi ASI dari semua perempuan yang mendonorkannya. Maka adanya bank ASI berlawanan dengan maqāṣid al-Sharī‘ah yang berupa menjaga nasab/ḥifẓ al-Nasb. Setelah mengkaji tentang pendirian bank ASI di Indonesia dengan melihat keadaan sosial yang beranekaragam serta rendahnya pemahaman masyarakat terhadap dampak persusuan (raḍāʽ) maka kelegalan bank ASI adalah sesuatu yang harus dicegah, (2) Kemungkinan besar terjadi pernikahan yang diharamkan, sebagai akibat dari percampuran ASI dari para pendonor, (3) Keterangan tim dokter yang menyatakan kebutuhan bank ASI tidak terlalu mendesak. Maka hukum pendirian bank ASI di Indonesia perspektif kaidah fikih dar’ al-Mafᾱsid muqaddam ʽalā jalb al-Maṣhāliḥ, maka dari ulasan di atas dapat disimpulkan bahwa haram hukum mendirikan bank ASI. Meninjau bahwa mudarat bank ASI lebih banyak daripada manfaatnya. Argumen yang menyatakan bahwa bank ASI urgen disebabkan banyaknya bencana alam, bayi prematur, dan lain sebagainya sesungguhnya telah dapat diatasi dengan menyusukan anaknya pada ibu susunya.